A fully degradable and photocrosslinked polysaccharide-polyphosphate hydrogel for tissue engineering. (1st December 2019) - Hao, Ying; He, Jinlin; Ma, Xun; Feng, Lin; Zhu, Mo; Zhai, Yuanxin; Liu, Yang; Ni, Peihong; Cheng, Guosheng
Graphical abstract: Highlights: Synthetic biodegradable copolymer PBYP- r -PEEP was successfully prepared. A fully degradable HA/PPE hydrogel was fabricated for stem cell encapsulation. HA/PPE hydrogel supported hMSCs growth and facilitated the cell-cell interactions. Abstract: Extracellular matrix degradability meditates cell behaviors and gains increasing importance in the development of implantation materials for tissue engineering. Here, we developed a fully biodegradable hydrogel combining the unique features of synthetic polyphosphate polymer and natural polysaccharide polymer. Polyphosphate copolymer poly(butynyl phospholane)- random -poly(ethylethylene phosphate) (PBYP- r -PEEP) bearing pendent alkynes was synthesized through a facile one-pot reaction. Subsequently, thiol-yne "click" reaction was employed to fabricate the fully degradable and photocrosslinked hydrogel by mixing PBYP- r -PEEP with thiolated biodegradable hyaluronic acid (HA-SH). The generated HA/PPE hydrogels show viscoelastic properties and enzymatic biodegradability, supporting the growth of human mesenchymal stem cells (hMSCs). HA/PPE hydrogel is permissive to the covalent conjugation of cell-adhesive peptide RGD, which can enhance the cell-cell interactions. This HA/PPE hydrogel system provides a fully biodegradable platform that can support hMSCs growth and facilitate the formation of cell clustering, expanding the range of fully degradable materials for tissue engineering and regenerative medicine.